Prayer card for Roger Casement (1916)
Inscription on card in ink under the text "Of your charity pray for the soul of", "Roger David Casement Aug. 3rd 1916 R.I.P". Inscription on verso "Eternal rest grant / him oh Lord / and let perpetual / light shine upon / him. / May his soul and all / the souls of the faithful / departed rest in / peace."
Keywords: Casement, Roger, -- 1864-1916 -- Death and burial